EVALUATING RESEARCH COLLABORATION IN X INSTITUTION - Bayu Indra Pratama; Muhammad Shobaruddin (Universitas Brawijaya, 2022)
Many studies have examined research collaboration related to research productivity and scientific publications. The tendency is that the higher the collaboration level, the higher the productivity. However, these studies do not always explain how the existing collaborations are formed. Even though lecturers in Indonesia have three responsibilities (Tridarma), which include education, research, and community service, these studies are also limited to the research aspect. The other two aspects are considered closely related because community service is considered as a downstream of research. Although qualitative studies can help explain the formation of research collaborations and community service, research on collaborations tends to use bibliometrics or social network analysis. This study seeks to explain the mapping and the formation of research collaborations at the X Institution, from 2020 to 2021, using bibliometric analysis combined with in-depth interviews with various stakeholders. Those years have been the initial period of using Research and Service Information Systems at the faculty level, so the availability of the data helps to describe the collaboration of research and community service at the X Institution. This mapping can be the basis for research and community service policies at the the X Institution.